Modeling and Simulation of a Novel Sustainable Ammonia Production Process From Food Waste and Brown Water - Ghavam, Seyedehhoma; Taylor, Caroline M.; Styring, Peter (Frontiers in Energy Research, 2021)
Global demand for both clean energy carriers and agricultural nutrients continues to grow rapidly, alongside increasing quantities of waste globally, interlinked challenges that may be addressed with interlinked solutions. We report on the potential efficiency and GHG intensity of several configurations of a new, sustainability-driven ammonia production processes to determine whether a waste-based process designed first around carbon dioxide capture can compete with other available ammonia technologies. This is assessed via different scenarios: two hydrogen generating options are paired with four CO2 fates. For either an anaerobic digestion-centered process or a two-stage dark fermentation coupled with anaerobic digestion process, the resultant CO2 may be captured and injected, sold to the marketplace, released directly in the atmosphere, or converted to urea to produce a green substitute for synthetic ammonia. Modeled yields range from 47 t NH3 when the resultant carbon dioxide is released or captured, or 3.8 t NH3 and 76.5 t urea when the system is designed to produce no unutilized carbon dioxide. Among the technologies assessed, ammonia production where CO2 is captured for anaerobic digestion-only is the most efficient for GHG emissions and water consumption, while the two-stage requires less energy on a fertilizer-N basis. GHG emissions for anaerobic digestion-only are approximately 8% lower than the two-stage. The best of the proposed technology configurations consumes about 41% less energy than water electrolysis coupled with Haber-Bosch and approximately 27% lower energy than steam methane reforming coupled with Haber-Bosch per kgNH3.